Standardizing Visual Control Devices for Tsetse Flies: West African Species Glossina tachinoides, G. palpalis gambiensis and G. morsitans submorsitans - Rayaisse, Jean-Baptiste; Kröber, Thomas; McMullin, Andrew; Solano, Philippe; Mihok, Steve; Guerin, Patrick (My University, 2012)
Here we describe field trials designed to standardize tools for the control of Glossina tachinoides, G. palpalis gambiensis and G. morsitans submorsitans submorsitans in West Africa based on existing trap/target/bait technology. Blue and black biconical and monoconical traps and 1 m2 targets were made in either phthalogen blue cotton, phthalogen blue cotton/polyester or turquoise blue polyester/viscose (all with a peak reflectance between 450–480 nm) and a black polyester. Because targets were covered in adhesive film, they proved to be significantly better trapping devices than either of the two trap types for all three species (up to 14 times more for Glossina tachinoides, 10 times more for G. palpalis gambiensis, and 6.5 times for G. morsitans submorsitans). The relative performance of the devices in the three blue cloths tested was the same when unbaited or baited with a mixture of phenols, 1-octen-3-ol and acetone. Since insecticide-impregnated devices act via contact with flies, we enumerated which device (traps or targets) served as the best object for flies to land on by also covering the cloth parts of traps with adhesive film. Despite the fact that the biconical trap proved to be the best landing device for the three species, the difference over the target (20–30%) was not significant. This experiment also allowed an estimation of trap efficiency, i.e. the proportion of flies landing on a trap that are caught in its cage. A low overall efficiency of the biconical or monoconical traps of between 11–24% was recorded for all three species. These results show that targets can be used as practical devices for population suppression of the three species studied. Biconical traps can be used for population monitoring, but a correction factor of 5–10 fold needs to be applied to captures to compensate for the poor trapping efficiency of this device for the three species.